Penyebaran Nilai-Nilai Lingkungan di Masyarakat Petani Pedesaan (Studi Etnografi Komunikasi pada Masyarakat Desa Tenam Bungkuk, Semende Darat Kabupaten Muara Enim, Provinsi Sumatera Selatan) - Yenrizal Yenrizal (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2017)
Environmental values prevailing in a society associated with a community perspective in viewing environment. These values look at society and the environment as a whole. The research looked at how these environmental values into a symbols are interpreted together and then disseminated throughout the community. There is a process of environmental communication that shows how human interaction with the natural environment, especially in rural communities. Through ethnographic methods of communication, the results of this study indicate that there is a process of meaning in society is the construction process on the environment. It is spread from one generation to the next through activities in accordance with the typology and characteristics of the community, namely Semende community. This deployment takes place naturally and follow routines residents, with the main viewpoint is the integrity and sustainability of the local environment.